The Ability of Alum to Reduce Color in Sasirangan Home Industry Wastewater - Khair, Abdul; Noraida, Noraida (Poltekkes Kemenkes Banjarmasin Jurusan Analis Kesehatan, 2025)
Water is the main need of living things in the world. Water determines the sustainability of living things. Humans, animals, and plants depend on water for their survival. Therefore, water should always meet the standards that have been set. Wastewater from the home-based sasirangan industry has distinctive characteristics in the form of the color of wastewater that has not been managed properly. The purpose of this study was to determine the ability of alum to reduce the color of home-based sasirangan industry wastewater. The type of research is a true experiment, with the population being all home-based sasirangan industry wastewater in Atun Sasirangan Cempaka. The sample is part of the wastewater. The wastewater was put into 25 containers for 5 treatments of alum addition with concentrations of 40%, 80%, 160%, 240%, and 320%. Each treatment was repeated 5 times. The results showed that the average value of wastewater color after treatment ranged from 140.5 to 179.2 Pt-Co. The lowest average value was in the treatment of adding alum with a concentration of 160%. It is concluded that alum is able to reduce the color of home-based sasirangan industry wastewater. It is recommended that the handling of wastewater color problems in the sasirangan fabric home industry use alum as a coagulant in the treatment method.